Petatah-Petitih Masyarakat Melayu Besemah dalam Perspektif Maqȃşid Syarî’ah - Ibrahim, Duski; Abun, A. Rifa’i; Meladiah, Rahmah (Medina-te : Jurnal Studi Islam, 2021)
The aim of the research is to analyze the content of the prayers of the people of Lahat Regency. The method that will be used in this research is qualitative. This approach was chosen because this type of qualitative research approach focuses on describing, analyzing and interpreting group culture. Apart from that, a historical approach will be used. The informants in this research are community figures, religious figures, who understand the adages in the Lahat Regency area. Then, in qualitative studies, the main research instrument is the researcher himself who is assisted by several implementers. The data mining techniques will be carried out by means of observation and in-depth interviews. Next, data regarding the substance of these sayings will be analyzed using content analysis. The results of this research found that based on the research we conducted with the framework and analysis used, information was obtained that the contents or messages contained in the sermons of the Besemah Malay community (with a few exceptions) were in line with Islamic teachings. In other words, the content of these sermons is a combination of the local culture of the Besemah Malay community, global culture and Islamic teachings, especially those related to society.